The Effect of Socialization Regarding Digital Literacy to Respond to Challenges in The Era of Disruption to The Knowledge of Students of Junior High School 12 Bandung - Alifia Ghaniya Zahra; Rina Maryanti (International Journal of Research and Applied Technology (INJURATECH), 2022)
This This study aims to find out how the impact of socialization on digital literacy to answer challenges in the era of disruption to knowledge and application in everyday life regarding digital literacy for students at Junior High School 12 Bandung. The situation in this era of disruption is increasing the use of social media as online media. Children and parents use social media a lot. Young people as the millennial generation or can also be called digital natives are the largest users in the use of social media today. The spread of social media networks makes it easier for inaccurate news to come from anywhere. It is hoped this research can add insight into appropriate digital literacy. The subjects of this study were students of Junior High School 12 Bandung as a young age group with an age range of 13-17 years who were active users of social media. Respondents amounted to 15 students. Respondents consisted of 5 students in grade 7, 1 student in grade 8, and 9 students in grade 9. This study used a quantitative descriptive method. The technique used for data collection is using a questionnaire. There are three stages in data collection, namely (i) distributing the pre-test questionnaire; (ii) providing socialization actions using powerpoint; and (iii) distribution of post-test questionnaires. The data processing approach used is a quantitative approach. The results showed there was an increase between the average pre-test and post-test values, namely an increase from the pre-test average value of 73.33 to 96, 44 on the post-test score / after receiving socialization treatment. The calculation of N-Gain is carried out to determine the effectiveness of the socialization carried out. The results show the average N-Gain value is 85% (N-Gain > 40%). It can be concluded the socialization of digital literacy using powerpoint media is effective for students of Junior High School 12 Bandung. Effective results due to lack of insight and interest in literacy in Junior High School 12 Bandung students are low and after the socialization treatment is given, it adds insight to students at JUNIOR HIGH SCHOOL 12 Bandung because the post-test scores of students increase significantly. It can be concluded the socialization of digital literacy using powerpoint media is effective for students of Junior High School 12 Bandung. Effective results due to lack of insight and interest in literacy in Junior High School 12 Bandung students are low and after the socialization treatment is given, it adds insight to students at Junior High School 12 Bandung because the post-test scores of students increase significantly. It can be concluded the socialization of digital literacy using powerpoint media is effective for students of Junior High School 12 Bandung. Effective results due to lack of insight and interest in literacy in Junior High School 12 Bandung students are low and after the socialization treatment is given, it adds insight to students at Junior High School 12 Bandung because the post-test scores of students increase significantly.